18F‐flortaucipir tau positron emission tomography distinguishes established progressive supranuclear palsy from controls and Parkinson disease: A multicenter study - Schonhaut, Daniel R.; McMillan, Corey T.; Spina, Salvatore; Dickerson, Bradford C.; Siderowf, Andrew; Devous, Michael D.; Tsai, Richard; Winer, Joseph; Russell, David S.; Litvan, Irene; Roberson, Erik D.; Seeley, William W.; et al. (Annals of neurology, 2017)
Objective 18F‐flortaucipir (formerly 18F‐AV1451 or 18F‐T807) binds to neurofibrillary tangles in Alzheimer disease, but tissue studies assessing binding to tau aggregates in progressive supranuclear palsy (PSP) have yielded mixed results. We compared in vivo 18F‐flortaucipir uptake in patients meeting clinical research criteria for PSP (n = 33) to normal controls (n = 46) and patients meeting criteria for Parkinson disease (PD; n = 26). Methods Participants underwent magnetic resonance imaging and positron emission tomography for amyloid‐β (11C‐PiB or 18F‐florbetapir) and tau (18F‐flortaucipir). 18F‐flortaucipir standardized uptake value ratios were calculated (t = 80–100 minutes, cerebellum gray matter reference). Voxelwise and region‐of‐interest group comparisons were performed in template space, with receiver operating characteristic curve analyses to assess single‐subject discrimination. Qualitative comparisons with postmortem tau are reported in 1 patient who died 9 months after 18F‐flortaucipir. Results Clinical PSP patients showed bilaterally elevated 18F‐flortaucipir uptake in globus pallidus, putamen, subthalamic nucleus, midbrain, and dentate nucleus relative to controls and PD patients (voxelwise p < 0.05 family wise error corrected). Globus pallidus binding best distinguished PSP patients from controls and PD (area under the curve [AUC] = 0.872 vs controls, AUC = 0.893 vs PD). PSP clinical severity did not correlate with 18F‐flortaucipir in any region. A patient with clinical PSP and pathological diagnosis of corticobasal degeneration had severe tau pathology in PSP‐related brain structures with good correspondence between in vivo 18F‐flortaucipir and postmortem tau neuropathology. Interpretation 18F‐flortaucipir uptake was elevated in PSP versus controls and PD patients in a pattern consistent with the expected distribution of tau pathology. Ann Neurol 2017;82:622–634